2020
DOI: 10.1038/s41588-020-0631-4
|View full text |Cite|
|
Sign up to set email alerts
|

Mendelian randomization accounting for correlated and uncorrelated pleiotropic effects using genome-wide summary statistics

Abstract: Mendelian randomization (MR) is a valuable tool for detecting causal effects using genetic variant associations. Opportunities to apply MR are growing rapidly with the number of genome-wide association studies (GWAS). However, existing MR methods rely on strong assumptions that are often violated, leading to false positives. Correlated horizontal pleiotropy, which arises when variants affect both traits through a heritable shared factor, remains a particularly challenging problem. We propose a new MR method, C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
562
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(576 citation statements)
references
References 32 publications
11
562
3
Order By: Relevance
“…In terms of results, in simulations we have seen that our approach remains robust (i.e. unbiased) to increased polygenicity (up to 100%) of the confounder U , while CAUSE has substantial false positive rate already when ⇡ u > 0.3 in samples of size 40,000 (see Fig4a of Morrison et al [10] ).…”
Section: Application To Association Summary Statistics Of Complex Traitsmentioning
confidence: 74%
See 1 more Smart Citation
“…In terms of results, in simulations we have seen that our approach remains robust (i.e. unbiased) to increased polygenicity (up to 100%) of the confounder U , while CAUSE has substantial false positive rate already when ⇡ u > 0.3 in samples of size 40,000 (see Fig4a of Morrison et al [10] ).…”
Section: Application To Association Summary Statistics Of Complex Traitsmentioning
confidence: 74%
“…However, such instruments will have a direct e↵ect on the outcome that is correlated to their instrument strength, violating the InSIDE assumption. A very recent approach (CAUSE) proposes a structural equation mixed e↵ect model [10] , similar to ours. In the Discussion, we will provide a detailed account of the di↵erences between CAUSE and our method.…”
Section: Introductionmentioning
confidence: 99%
“…A Mendelian randomization (MR) approach is one possible avenue to address confounding issues. Lipids and CHD have been investigated using MR, and the results suggest a causal association between LDL and increased CHD but a null association for HDL . Less investigated is the association between lipids and other competing risks, and more broadly, survival to old age.…”
Section: Discussionmentioning
confidence: 99%
“…Finally unlike both, we are able to estimate both effect directions simultaneously, allowing our model to accommodate graphs with cycles. Our method is also related to the recently proposed CAUSE [55]. There, the authors model observed SNPs effects as coming from a mixture of pleiotropic and non-pleiotropic SNPs.…”
Section: Discussionmentioning
confidence: 99%